Diarrhoea in children under five years of age in South Africa (1997–2014). Issue 9 (6th July 2016) - Awotiwon, Oluwatoyin F.; Pillay‐van Wyk, Victoria; Dhansay, Ali; Day, Candy; Bradshaw, Debbie
Abstract: Objective: To present evidence from available reliable published data on the prevalence, incidence and severity of diarrhoea in children aged under five years in South Africa. Methods: We searched seven electronic databases. Two reviewers assessed the studies independently and extracted outcome data. The heterogeneity of the studies did not allow for a meta‐analysis. Results: We found only one nationally representative study conducted in 1998 reporting a diarrhoea prevalence of 13% in children under five. Other studies were conducted in smaller settings across the country. Diarrhoea incidence was 10.13 per 1000 person years in children admitted to a tertiary hospital. Three studies reported severity of diarrhoea; however, they differed across study settings and time period. Conclusion: The paucity of nationally representative prevalence data for SA necessitates more national surveys with standardised data‐collection methods to allow for more effective comparisons.